Computing Ellipsoidal Robust Forward Invariant Tubes for Nonlinear MPC. Issue 1 (July 2017) - Villanueva, Mario E.; Li, Jiaqi C.; Feng, Xuhui; Chachuat, Benoît; Houska, Boris
Abstract: Min-max differential inequalities (DIs) can be used to characterize robust forward invariant tubes with convex cross-section for a large class of nonlinear control systems. The advantage of using set-propagation over other existing approaches for tube MPC is that they avoid the discretization of control policies. Instead, the conservatism of min-max DIs in tube MPC arises from the discretization of sets in the state-space, while the control law is never discretized and remains defined implicitly via the solution of a min-max optimization problem. The contribution of this paper is the development of a practical implementation of min-max DIs for tube MPC using ellipsoidal-tube enclosures. We illustrate these developments with a spring-mass-damper system.